The oxidative pentose phosphate pathway: structure and organisation. - Kruger, N; von Schaewen, A (2003)
The oxidative pentose phosphate pathway is a major source of reducing power and metabolic intermediates for biosynthetic processes. Some, if not all, of the enzymes of the pathway are found in both the cytosol and plastids, although the precise distribution of their activities varies. The apparent absence of sections of the pathway from the cytosol potentially complicates metabolism. These complications are partly offset, however, by exchange of intermediates between the cytosol and the plastids through the activities of a family of plastid phosphate translocators. Molecular analysis is confirming the widespread presence of multiple genes encoding each of the enzymes of the oxidative pentose phosphate pathway. Differential expression of these isozymes may ensure that the kinetic properties of the activity that catalyses a specific reaction match the metabolic requirements of a particular tissue. This hypothesis can be tested thanks to recent developments in the application of 13C-steady-state labelling strategies. These strategies make it possible to quantify flux through metabolic networks and to discriminate between pathways of carbohydrate oxidation in the cytosol and plastids.